1980
DOI: 10.1136/gut.21.11.951
|View full text |Cite
|
Sign up to set email alerts
|

Studies on breath methane: the effect of ethnic origins and lactulose.

Abstract: SUMMARY The prevalence of methane production in an adult population of 256 subjects was 41%, but it was significantly higher in females (49 %), than males (33 %). When the population was subdivided into ethnic groups, Caucasians (48 %) and Blacks (45 %) had significantly more methane producers than Orientals (24%) and Indians (32 %). When the ethnic groups were analysed by sex, female Caucasians had the highest prevalence (58 %), significantly more than Caucasian males, Oriental males, and females and Indian m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
2

Year Published

1985
1985
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(50 citation statements)
references
References 7 publications
2
46
0
2
Order By: Relevance
“…CH, exhalation occurs at relatively constant rates (Bond et al 1971 ;Tadesse & Eastwood, 1978;Pitt et al 1980;Tadesse et al 1980;Bjnrneklett & Jenssen, 1982), as was also observed in the present investigation ( Fig. 3(a)) during 10 h when no sharp meal-related peak was found.…”
Section: Discussionsupporting
confidence: 86%
“…CH, exhalation occurs at relatively constant rates (Bond et al 1971 ;Tadesse & Eastwood, 1978;Pitt et al 1980;Tadesse et al 1980;Bjnrneklett & Jenssen, 1982), as was also observed in the present investigation ( Fig. 3(a)) during 10 h when no sharp meal-related peak was found.…”
Section: Discussionsupporting
confidence: 86%
“…Methane excretion phenotyping of 274 Australian families containing adolescent twin pairs indicated that environmental exposures play a deterministic role in methanogen carriage, with similar concordance and correlations between MZ and DZ co-twins, and less concordance between parents and their offspring (17). As in other studies (18), more females than males had positive methane breath tests. Studies of intergenerational transfer of a positive methane excretion phenotype in rats demonstrated the critical effects of environmental factors during the weaning period; however, colonization through adulthood varied between strains of rats (17), suggesting that host genetic factors affect carriage.…”
mentioning
confidence: 49%
“…A female bias (p ϭ 0.012) for methanogenesis (63% females vs 37% males), which has been found in most studies (6,17,21,22,32), is unlikely to be a chance finding. The modeling, although distinguishing genetic and environmental effects within same sex subjects, cannot discriminate between genetic and behavioral effects that associate with the Y chromosome (or conversely with the X chromosome).…”
Section: Discussionmentioning
confidence: 92%